Chemical and isotopic composition of magmatic gases from the 1988 eruption of Klyuchevskoy volcano, Kamchatka - Taran Yu.A.; Rozhkov A.M.; Serafimova E.K.; Esikov A.D. (Journal of Volcanology and Geothermal Research, 1991)
Gas samples have been collected at the place of magma effusion during the 1988 flank eruption of Klyuchevskoy, for the first time in the course of studies at this volcano. The high-temperature gases (1000–1100°C) are rich in water and halogens but depleted in sulphur. Their molar composition is close to chemical equilibrium at the collection temperature, while their oxidation state corresponds to redox conditions between FMO and NNO buffers. The isotopic composition of the water (δD = −71 to −44‰; δ18O = +6.3 to +8.4‰, versus SMOW) plots within the field of “primary magmatic” waters. The isotopic composition of H2 (δD = −187‰ to −160‰) is consistent with isotopic equilibrium between H2 and H2O in the conditions of emission. Both the chemistry of the gases and the low δ13C of carbon dioxide (−11.6‰, PDB) suggest extensive magma outgassing occurred during the course of the eruption.